Pengaruh Data Mining, Strategi Perusahaan, Terhadap Laporan Kinerja Perusahaan - Haryanti, Mayang Fadillah; Fauzi, Achmad; Jelita, Alvina Arum; Setiyowati, Anggi; Octarina, Azzahra; Edina, Edo Putra; Aulia, Reva Zahra; Fitriana, Sela (Prisani Cendekia, 2024)
The rapid development of business in the digital era intensifies competition among companies. To survive, businesses must develop effective sales strategies based on accurate information. This study explores the impact of strategic datamining on company performance. Data mining techniques, such as classification and forecasting, help analyze sales data to predict trends, enabling production adjustments and sales optimization. Implementing data mining accelerates decision-making, increases sales, and reduces losses, making companies more competitive. Data mining is the process of extracting valuable information from large datasets, crucial for business improvement. It transforms transactional data into actionable insights, enabling automated and efficient analysis. This study shows that data mining enhances operational efficiency, data-driven decision-making, and predictive capabilities. Challenges like technical complexity and data quality must be addressed. In conclusion, data mining plays a vital role in improving company performance by identifying patterns, optimizing operations, and predicting future trends. This allows companies to enhance efficiency and competitive